Pengaruh Hukum Islam tentang Larangan Tuak Terhadap Perilaku Masyarakat Desa Boto Kecamatan Semanding - Husni Habibi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2019)
This article is based on field research aims to answer the question of the influence of Islamic Law on prohibiting liquor (Tuak) towards community behavior of Boto Village in Semanding district of Tuban Regency. It also strives to analyze the factors that contribute to mold people's behavior. The approach of this research is combining a quantitative survey and qualitative research methods, with data analysis techniques in the form of analytical descriptive. The results of the study conclude that Islamic law is incapable of fashioning the actual behavior of its adherents, especially in the village of Boto. The prohibitions of liquor (tuak) failed to stimulate the behavior of rural communities under Islamic legal norms. This is indicated by the lack of community response to Islamic legal norms. On the contrary, it is conclusively found that the behavior of the majority of people deviates from the Islamic provisions of legal norms about the prohibition of liquor (tuak).